Clinical outcomes of salvage radiotherapy in patients with supraclavicular lymph node metastases after esophagectomy - Ping, Zhang; Chanjun, Zhen; Wenwen, Bai; Mingyue, Chen; Quanbing, Su; Yajing, Wang; Zhiguo, Zhou (Frontiers in Oncology, 2023)
Purpose: To evaluate the clinical outcomes of salvage radiotherapy in patients with supraclavicular lymph node (SCLN) metastases after esophagectomy. Methods: After initial esophagectomy (R0 resection), clinical outcomes in patients with esophageal squamous cell carcinoma with SCLN metastases during follow-up were retrospectively analyzed. Results: A total of 114 patients were split into two groups: the salvage radiotherapy (SR) (n=89) and the control (NSR) (without salvage radiotherapy, n=25). The overall survival rates of 1 year, 3 years and 5 years were 81.6%, 31.4% and 8.6%, accordingly. 40.2% of patients after SCLN metastasis (SASM) survived 1-year and 14.5% survived 3-year, with the median SASM duration of 10 months. In the SR group, the SASM rates of 1-year and 3-year were, respectively, 48.1% and 18.9%, compared to 12.0% and 0% in the NSR group (p<0.001). Patients in the SR group who received combined radiochemotherapy experienced 1-year and 3-year SASM rates of 62.6% and 33.4%, compared to 41.9% and 16.5% with single radiotherapy (p<0.001). From the subgroup analysis, the 1-year and 3-year SASM rates turned out to be 35.5% and 0% in the combined visceral metastases (CVM) group, whereas the non-combined visceral metastases group (NCVM) had a rate of 42.3% and 21.5%(p=0.004). The SASM rate of 3-year patients(22.2%) in the non-combined mediastinal failure (NCMF) group was higher than that (7.0%) of patients in the combined mediastinal failure (CMF) group (p=0.041). The salvage radiation dose revealed that the 1-year and 3-year SASM rates turned out to be 56.5% and 23.4% in group of ≥60 Gy, and 29.2% and 7.5% in group of <60 Gy (p<0.001). According to multivariate analysis, combined visceral metastases, combined mediastinal failure, salvage radiotherapy, salvage radiation dose and salvage treatment method possibly were identified as important prognostic variables. Conclusion: It is possible that salvage radiotherapy can increase the survival rate of patients who receive SCLN metastases following esophagectomy.